2022
DOI: 10.1097/md.0000000000030027
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA expression profiling in adenocarcinoma and squamous cell lung carcinoma reveals both common and specific deregulated microRNAs

Abstract: The current study investigated the expression signatures of miRNAs in lung adenocarcinoma (LUAD) and squamous cell lung carcinoma (LUSC). miRNA profiling was performed using microarray in 12 LUAD and 12 LUSC samples and adjacent normal tissues. In LUAD, 107 miRNAs were significantly deregulated, whereas 235 miRNAs were deregulated in LUSC. Twenty-six miRNAs were common between the 2 cancer subtypes and 8 were prioritized for validation, in addition to 6 subtype-specific miRNAs. The RT-qPCR validation samples i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…For LUSC patients, Yang et al ( Yang et al, 2010 ) reported the significance of nine miRNAs (miR-30d, miR-185, miR-30a, miR-193a-3p, miR-125a, miR-101, let-7i, miR-126, and miR-15a) by using real-time polymerase chain reaction (qRT-PCR) in their studies. In another study, Petkova et al ( Petkova et al, 2022 ) validated 10 miRNAs (miR-144-3p, miR-4689-3p, miR-7-5p, miR-744-3p, miR-650, miR-375, miR-140-3p, miR-195-5p, miR-95-5p and miR-21-3p) related to LUSC.…”
Section: Discussionmentioning
confidence: 98%
“…For LUSC patients, Yang et al ( Yang et al, 2010 ) reported the significance of nine miRNAs (miR-30d, miR-185, miR-30a, miR-193a-3p, miR-125a, miR-101, let-7i, miR-126, and miR-15a) by using real-time polymerase chain reaction (qRT-PCR) in their studies. In another study, Petkova et al ( Petkova et al, 2022 ) validated 10 miRNAs (miR-144-3p, miR-4689-3p, miR-7-5p, miR-744-3p, miR-650, miR-375, miR-140-3p, miR-195-5p, miR-95-5p and miR-21-3p) related to LUSC.…”
Section: Discussionmentioning
confidence: 98%
“…33 Petkova et al reported the downregulation of several miRNAs in NSCLC tissues, including miR-140-3p. 34 Additionally, miR-140-3p downregulation predicted poor prognosis in lung adenocarcinoma. 19 On the contrary, Vykoukal et al demonstrated miR-140-3p was overexpressed in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Others are upregulated and act as oncogenes in NSCLC 33 . Petkova et al reported the downregulation of several miRNAs in NSCLC tissues, including miR‐140‐3p 34 . Additionally, miR‐140‐3p downregulation predicted poor prognosis in lung adenocarcinoma 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, it has been also shown that the miR-193 family plays a role in the pathological processes underlying cardiovascular disorders [9]. It has been reported that miR-193b-3p is among the targets of PAPR1 [10]. miR-21-5p is highly expressed in the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%